The role of diagnostic laparoscopy in the era of modern imaging techniques: a study from a single center - Parray, Muzafar Yousuf; Malik, Ajaz Ahmad; Hassan, Yaqoob; Wani, Ishfaq Ahmad; Ahmad Wani, Munir Ahmad; Bashir, Wani Shahid (International Surgery Journal, 2019)
Background: Despite the tremendous progressive evolution in the field of medicine, wherein, most of the diseases can be diagnosed based on history, clinical examination and investigations, there are quite a number of diseases which remain undiagnosed. It is here, where the role of diagnostic laparoscopy becomes important to reach to a conclusion for further management of patients. Methods: This study comprising of 70 patients undergoing diagnostic laparoscopy at SKIMS over a period of 4 years. This study was done to evaluate the role of diagnostic laparoscopy in patients with acute and chronic abdominal conditions wherein final diagnosis could not be achieved after all necessary imaging, serological, cytological, and microbiological investigations. Results: Out of 70 patients subjected to diagnostic laparoscopy in our study, the commonest indication was as cites of undetermined etiology (42.9%) followed by chronic abdominal pain (25.7%) diffuse liver disease (11.4%) acute abdominal pain (SAIO, cholecystitis, acute appendicitis, PID, endometriosis) (5.7%) abdominal tuberculosis (4.3%) focal liver disease (2.9%) bleeding per rectum (2.9%) abdominal malignancy (2.9%) and primary infertility (1.4)%. The post diagnostic laparoscopy outcome (final diagnosis) were abdominal malignancy 22 (31.4%) followed by abdominal tuberculosis 16 (22.9%) diffuse liver disease 6 (8.6%) focal liver disease 6 (8.6%) PID 4 (5.7%) SAIO 4 (5.7%) post-operative pelvic adhesions 3 (4.3%) Meckel’s diverticulum 2 (2.9%) abdominal plus pulmonary tuberculosis 1 (1.4%), endometriosis 1 (1.4%), ovarian cyst 1 (1.4%), pseudomyxoma peritonei 1 (1.4%), chronic appendicitis 1 (1.4%) and inconclusive 2 (2.9%). Diagnostic laparoscopy confirmed pre-operative diagnosis in 10 (14.3%) patients. In 29 (41.4%) patients pre-operative diagnosis was corrected by diagnostic laparoscopy. In 29 (41.4%) patients diagnosis was made only after diagnostic laparoscopy. Conclusions: Diagnostic laparoscopy is a safe, quick, and effective adjunct to non surgical diagnostic modalities, for establishing a conclusive diagnosis with high percentage of accuracy in diagnosis and impact in further management in selected patients.